Preparation of complexes of 1-amino-6,7-O-cyclohexylidene-4-azaheptane with transition metal acetates - Öztirk, OF; Sekerci, M; Özdemir, E (Pleiades Publishing Ltd, 2006)
1-Amino-6,7-O-cyclohexylidene-4-azaheptane (L) has been synthesized starting from 1-chloro-2,3-O-cyclohexylidenepropane prepared by the reaction of epichlorohydrin with cyclohexanone, catalyzed by BF3OEt2, Complexes of this ligand with Co(II), Ni(II) and Cu(II) acetates were prepared. The structures of the ligand and its complexes are proposed based on the elemental analyses, IR, UV-VIS, and H-1 and C-13 NMR spectra, magnetic susceptibilities, and conductomety data.
Keywords: Uo2(Vi) Complexes; Cu(Ii); Co(Ii); Ni(Ii)